Transformation of Islamic Education Based on Artificial Intelligence: Opportunities and Ethics in Character Building for Students - Zahwa Aqilah Muzarajo Putri; Zulvahmi Amran; Rachmat Fatdilla; Herviqa Agriana; Agustin Nurul Rohima; Lidia Wati; Hamzah Irfanda (Penerbit Presisi Pustaka, 2026)
The transformation of Islamic education in the digital era brings both significant opportunities and challenges, particularly with the advent of Artificial Intelligence (AI). AI can enhance learning efficiency, enable curriculum personalization to meet students’ needs, and expand access to education. On the other hand, its use raises fundamental ethical questions regarding the teacher’s role as a moral exemplar, students’ spirituality, and the potential dehumanization of the educational process.This study explores how AI can be strategically implemented in Islamic education while preserving moral and ethical values. Employing a qualitative method with a library research approach, it analyzes scientific literature, international journals, and scholars’ perspectives on AI in education. The findings reveal that AI has great potential as a tool for transforming Islamic education, but its use must be guided by Islamic ethical principles, including tawhid (divine unity), amanah (trustworthiness), and social responsibility.Therefore, AI-based transformation in Islamic education is not merely technological modernization, but an opportunity to strengthen humanistic values and moral development. Its implementation must balance innovation with nurturing students’ spiritual and ethical growth, ensuring that technology supports rather than replaces the teacher’s role and the core values of Islamic education.